Utilizing direct skin feeding assays for development of vaccines that interrupt malaria transmission: A systematic review of methods and case study. Issue 48 (21st November 2016) - Brickley, Elizabeth B.; Coulibaly, Mamadou; Gabriel, Erin E.; Healy, Sara A.; Hume, Jen C.C.; Sagara, Issaka; Traore, Sekou F.; Doumbo, Ogobara; Duffy, Patrick E.
Highlights: Vaccines that interrupt malaria transmission (VIMTs) suppress human infectivity. Direct skin feeding assays (DSFs) quantify transmission-blocking activity of VIMTs. DSFs are adaptable to heterogeneous settings, but methods require standardization. Statistical power is the key limitation for evaluating vaccine activity with DSFs. Abstract: Shifting the malaria priorities from a paradigm of control and elimination to a goal of global eradication calls for renewed attention to the interruption of malaria transmission. Sustained progress toward eradication will require both improved understanding of infectious reservoirs and efficient development of novel transmission-blocking interventions, such as rapidly acting and highly efficacious therapeutics and vaccines. Here, we review the direct skin feeding assay (DSF), which has been proposed as a valuable tool for measuring the in natura transmission of malaria parasites from human hosts to mosquito vectors across heterogeneous populations. To capture the methodological breadth of this assay's use, we first systematically review and qualitatively synthesize previously published investigations using DSFs to study malaria transmission in humans. Then, using a recent Phase 1 trial in Mali of the Pfs25H-EPA/Alhydrogel® vaccine candidate (NCT01867463) designed to interrupt Plasmodium falciparum transmission as a case study, we describe the potential opportunities and current limitations of utilizing the endpoints measured by DSF in making early clinical decisions for individually randomized transmission-interrupting intervention candidates. Using simulations based on the data collected in the clinical trial, we demonstrate that the capacity of the DSF to serve as an evaluative tool is limited by the statistical power constraints of the "effective sample size" (i.e. the number of subjects that are capable of transmitting at the time of feeding). Altogether, our findings suggest DSFs have great potential utility for assessing the public health impacts of emerging antimalarial tools, but additional research is needed to address issues of scalability and to establish correlation with community-wide clinical endpoints as well as complementary in vitro measures, such as standard membrane feeding assays.